Transformation of Social Structure in Digital Society: Analysis of Network Sociology - Aliah Amalyah (Mahogany Journal De Social, 2025)
This study examines the transformation of social structures in digital society through a quantitative approach integrating social network analysis and survey data. Using a sample of 200 active social media users in major Indonesian cities, the research maps relational patterns, measures centrality, and evaluates network density and modularity to understand how digital interactions shape social cohesion, identity, and influence. Findings indicate that digital platforms facilitate the formation of new solidarities and broaden participation, yet they do not fully replace offline identities. At the same time, interaction is concentrated around key actors and shaped by platform algorithms, revealing persistent hierarchies and structural inequalities. The study highlights the ambivalent nature of digital social spaces, where connectivity coexists with fragmentation, and underscores the role of digital networks in actively constructing social meaning. These insights contribute to understanding the complex dynamics of social transformation in the digital era and provide a foundation for future research on hybrid social structures.